Planning and assessment in higher education : demonstrating institutional effectiveness - Middaugh, Michael F., 1945- (San Francisco : Jossey-Bass, 2010)
"This book helps colleges and universities respond to the increasing pressures for accountability by giving them the tools to demonstrate institutional effectiveness. The author is in a unique position to help his colleagues, since he comes at the topic from multiple perspectives, being both a leading practitioner and researcher: Assistant VP for Institutional Research and Planning at his university, director of a national research project on costs of instruction, as well as Vice Chair of an accreditation agency. While many books address the issue of assessing student learning outcomes, this book provides expert guidance for assessing and promoting institutional effectiveness in supporting student learning. The book's chapters cover every aspect from the overall context of the issue, through measures of effectiveness, to communicating with the public, and concludes with a guide to resources"--Provided by publisher.
The national context for assessment -- Starting at the beginning: mission-driven planning and assessment -- Assessing institutional effectiveness: student issues -- A core issue in institutional effectiveness: developing sensible measures of student learning -- Maximizing human and fiscal resources in support of the teaching/learning process -- A comparative context for examining data on teaching loads and instructional costs -- measuring administrative effectiveness -- Communicating assessment results -- Where do we go from here?
Includes bibliographical references and index.
1 2
Keywords: Education, Higher -- Planning; Universities and colleges -- Administration; Education, Higher -- Standards; Education, Higher -- Economic aspects; Educational evaluation; Educational accountability